Palmar hyperhidrosis: Clinical, pathophysiological, diagnostic and therapeutic aspects - Romero, Flávio Ramalho [UNESP]; Haddad, Gabriela Roncada [UNESP]; Miot, Hélio Amante [UNESP]; Cataneo, Daniele Cristina [UNESP] (FapUNIFESP (SciELO), 2016)
Palmar hyperhidrosis affects up to 3% of the population and inflict significant impact on quality of life. It is characterized by chronic excessive sweating, not related to the necessity of heat loss. It evolves from a localized hyperactivity of the sympathetic autonomic system and can be triggered by stressful events. In this study, the authors discuss clinical findings, pathophysiological, diagnostic and therapeutic issues (clinical and surgical) related to palmar hyperhidrosis.
Keywords: Botulinum toxins; Cholinergic antagonists; Hyperhidrosis; Pulsed radiofrequency treatment; Sweating; Sympathectomy